2021
DOI: 10.3205/zma001516
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ mental burden and experiences of voluntary work in COVID-19 patient support and treatment services: a qualitative analysis

Abstract: Aim: Medical training is undergoing a dramatic shift toward alternative training methods due to the SARS-CoV-2 pandemic. This study is the first to examine medical students' expectations, experiences, and mental burden related to volunteering in COVID-19 patient support and treatment services using semi-structured interviews. Methods: In May 2020, all 194 Heidelberg University Medical School students involved in volunteer COVID-19 support and treatment services were invited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The theme of voluntarily taking care for Covid-19 patients, which emerged in the material, was previously described by Mu ¨hlbauer et al [42], who identified the wish to help and a sense for duty as the most important reasons. Nikendei et al [43] reported on the benefits of taking part in the care of Covid-19 patients in terms of personal growth and identification with the profession, which could be partly found in our material. The reported lack of fear of becoming infected and experiencing a severe course is in line with findings from the United States [44], which reported a comparably lower perceived risk in young adults with academic education.…”
Section: Plos Onesupporting
confidence: 56%
“…The theme of voluntarily taking care for Covid-19 patients, which emerged in the material, was previously described by Mu ¨hlbauer et al [42], who identified the wish to help and a sense for duty as the most important reasons. Nikendei et al [43] reported on the benefits of taking part in the care of Covid-19 patients in terms of personal growth and identification with the profession, which could be partly found in our material. The reported lack of fear of becoming infected and experiencing a severe course is in line with findings from the United States [44], which reported a comparably lower perceived risk in young adults with academic education.…”
Section: Plos Onesupporting
confidence: 56%
“…Following the positive impression of volunteering activity, three studies found a high level of willingness (73.2–94%) among health professional students regarding participation in the future ( 7 , 49 , 53 ). Regarding mental issues associated with volunteering, four studies found that student volunteers had low psychological stress ( 40 , 44 , 51 , 55 ). The prevalence of anxiety and depression was lower among volunteering students than non-volunteering ones, indicating that it positively influenced general psychological wellbeing ( 40 , 51 ).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study showed that volunteers feel uncertainty and apprehension when they started their work in COVID-19 settings. [ 22 ] Moreover, although medical students are vulnerable to mental health problems, health professionals may also develop a nonchalant attitude toward them. [ 23 , 24 ] Importantly, the uncertainty caused by anxiety and the ability to cope with it vary between individuals.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on the mental burden of medical students in Germany showed that most students would like to have access to more extensive preparation, such as task guidelines or informational videos, which could address their initial uncertainties. [ 22 ] It is therefore necessary to provide students with adequate training and information before they start their work.…”
Section: Discussionmentioning
confidence: 99%